Demographic and Socio-Economic Characteristics of Student Migration in Nepal - Khapangi, Madhav Bahadur (Kutumbha vani, 2024)
Student migration, defined as the movement of students to pursue education abroad for at least a year outside their country of citizenship, has transformed into a market-driven phenomenon due to the globalization of higher education. As the demand for international education surges, an increasing number of students perceive it as a pathway to potential permanent residency. The cultural and economic contributions of these international students have prompted stakeholders to facilitate their entry and integration. While North America, Europe, Australia, New Zealand, and East and Southeast Asia remain primary destinations, emerging educational hubs like Malaysia, the United Arab Emirates, and Singapore are witnessing a rise in international student enrollment. Nepal is a microcosm of this global trend, with thousands of its citizens pursuing higher education abroad annually. A comprehensive analysis of the demographic and socioeconomic characteristics of Nepalese students studying abroad reveals complex patterns influenced by factors such as geographic origin, gender, age, religion, marital status, and economic background. The preference for countries like Japan, characterized by favorable policies and educational opportunities, is particularly pronounced among students from regions like Lumbini and Madesh. These disparities underscore the persistence of sociocultural barriers hindering educational opportunities for women and the inequitable access to international education among students from different socioeconomic strata. To effectively support Nepalese students abroad, it is imperative to develop tailored policies and support systems that address the diverse needs and backgrounds of this population.